2007
DOI: 10.2353/ajpath.2007.051276
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Noggin Expression by Cancer Cells Is a Determinant of the Osteoblast Response in Bone Metastases

Abstract: Prostate and mammary cancer are among the leading cancers diagnosed and the second leading cause of cancer death in men and women, respectively.1 Both cancers show a high propensity to metastasize to bone. Whereas prostate cancer (CaP) elicits predominantly an osteoblast response resulting in osteosclerotic lesions, mammary cancer (CaM) triggers preferentially an osteoclast reaction with bone resorption and consequent osteolytic lesions.2 Osteolytic and osteosclerotic lesions are prone to pathological fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 67 publications
8
80
1
Order By: Relevance
“…Previously, we have shown that MDA-MB-231 breast cancer cells express relatively high amounts of Noggin (Schwaninger et al, 2007). A Noggin small interfering RNA significantly further increased Smad-dependent BMP signaling under the BMP2-stimulated conditions (BMP2, þ 52%, Po0.001), but no significant effects were observed under the BMP7-and BMP2/7-stimulated conditions (BMP7, þ 18%, NS; BMP2/7, þ 14%, NS) when compared with an non-targeted small interfering RNA (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that MDA-MB-231 breast cancer cells express relatively high amounts of Noggin (Schwaninger et al, 2007). A Noggin small interfering RNA significantly further increased Smad-dependent BMP signaling under the BMP2-stimulated conditions (BMP2, þ 52%, Po0.001), but no significant effects were observed under the BMP7-and BMP2/7-stimulated conditions (BMP7, þ 18%, NS; BMP2/7, þ 14%, NS) when compared with an non-targeted small interfering RNA (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the inhibitory effect of Noggin on BMP7, and particularly BMP2/7, was less prominent. Osteolytic MDA-MB-231 breast cancer cells express relatively high amounts of Noggin (Schwaninger et al, 2007), which directly contributes to an osteolytic bone phenotype through inhibition of BMP-mediated effects on bone formation by osteoprogenitors. The observed increased potency of BMP2/7 (compared with BMP2 or BMP7 alone) may, therefore, at least in part be caused by the increase in bioavailability due to the diminished efficacy of locally produced Noggin.…”
Section: Bmp2/7 Inhibits the Breast Cancer Stem Cell Subpopulation Jtmentioning
confidence: 99%
“…This indicates that functional TGF␤ and BMP receptors are present in these cells, thus confirming our earlier observations. 22,24 Exogenous addition of BMP7 but not of TGF␤ strongly stimulated BRE 4 -luciferase activity in PC-3M-Pro4 cells and indicated the presence of functioning, activated type 1 BMP-receptor complexes in these prostate cancer cells (Figure 5b). Strikingly, when BMP7 and TGF␤ were given simultaneously, BRE 4 -luciferase activity was significantly stimulated in a synergistic manner (Figure 5b).…”
Section: Bmp7 and Epithelial-to-mesenchymal Transition In Prostate Camentioning
confidence: 99%
“…BMP7 mRNA levels in prostate cancer cell lines strongly correlated to E-cadherin/vimentin ratio (Figure 2, a and b), whereas no association was observed for other BMPs (results not shown). 24 The highly tumorigenic and metastatic human prostate cancer cell line PC-3 and its derivative PC-3M-Pro4 did not show detectable BMP7 mRNA expression (Figure 2b) and protein synthesis in vitro (human specific BMP7 enzyme-linked immunosorbent assay; all Ͻ10 pg/ml hBMP7, n ϭ 4). The lack of BMP7 expression by PC-3M-Pro4 cells in vitro was confirmed in vivo in bone metastases (Figure 2d), suggesting that the bone microenvironment is unable to induce BMP7 expression in metastatic cancer cells.…”
Section: Bmp7 Mrna Expression In Prostate Cancer Cell Linesmentioning
confidence: 99%
“…Conversely, the induction of Dkk-1 in the mixed osteoblastic/osteolytic prostate cancer C4-2B cell line results in experimental bone metastases with an osteolytic phenotype in vivo. Dickkopf-1 expression in human breast cancer cell lines has been recently reported at mRNA level (Schwaninger et al, 2007).…”
mentioning
confidence: 99%